Pengaruh Kie KB Dalam Kelas Ibu Hamil Terhadap Pengetahuan dan Sikap Ibu Tentang KB Jangka Panjang di Puskesmas Buaran - Yuliana Eti Murdia Wanti; Desi Soraya; Qomariyah Qomariyah (Jurnal Anestesi, 2024)
Introduction: achievements every year, most acceptors prefer short-term contraceptive methods to long-term ones. Communication Information Education (CIE) is a very important aspect of family planning services so that officers can assist clients in choosing the contraception used. In this systematic and ongoing class of pregnant women, pregnant women can be involved in systematic and thorough discussions and exchange experiences. Objective: this study aimed to determine the effect of Communication Information Education (CIE) in the pregnant women's class on mothers' knowledge and attitudes about long-term family planning. Methods: this type of research was a quantitative study with a pre-experimental one-group pre-test, and post-test design. Population: the population was all third-trimester pregnant women at the Buaran Health Center, with as many as 94 pregnant women. Sample: all samples were given interventions in the form of Communication Information Education (CIE) in the class of pregnant women and given a questionnaire about their knowledge and attitudes about long-term family planning before and after the intervention. Analysis of the research data was carried out univariately using frequency distribution and bivariately using the Paired Sample t-test Results: to obtain a knowledge result of p-value 0.000 (p-value <0.05) and an attitude result of p-value 0.000 (p-value < 0.05), meaning that there was an influence of CIE in the class of pregnant women on mothers' knowledge about long-term family planning and an effect of CIE in the class of pregnant women on mothers' attitudes about long-term family planning.